Synthesis and characterization of tin-modified mesoporous silica MCM-48 for selective oxidation of alcohol to aldehyde - Ka Lun, Wong (2007)
Tin-modified mesoporous silica MCM-48 with various Si/Sn ratios has been prepared by post synthesis modification in alkaline medium. Local rice husk ash (RHA) has been used as Si precursor in the synthesis of Si-MCM-48 samples while SnCl2 was used as the tin source in the modification. The tin-modified MCM-48 samples were characterized by using powder X-ray diffraction (XRD) analysis, Fourier transform infrared (FTIR) spectroscopy, ultraviolet-visible diffuse reflectance (UV-Vis DR) spectroscopy, nitrogen physisorption measurement, field emission scanning electron microscopy (FESEM) and temperature-programmed reduction (TPR) analysis. Surface acidity of the prepared samples was determined by using pyridine adsorption-desorption measurement followed by FTIR spectroscopy. In addition, thermal and hydrothermal stability testing for the tin-modified samples were carried out. The FTIR, UV-Vis DR and XRD results show that tetrahedral tin species can be introduced into the mesoporous material without destroying the framework structure of the molecular sieves. Surface acidity studies confirm that Lewis acid sites had been generated on the mesoporous silica MCM-48 by post-synthesis modification. The generation of Lewis acid sites could be due to the introduction of tin species and/or because of defect sites that had been created during post-synthesis modification. Tin-modified sample SnM60 (Si/Sn = 60) possessed highest amount of Lewis acidity. In oxidation of benzyl alcohol, all the tinmodified samples gave 100% selectivity to benzaldehyde in reaction time under 22 hours. The catalytic activity can be correlated with the Lewis acid sites generated by post-synthesis modification. Purely siliceous MCM-48 and physically mixed tincontaining MCM-48 samples that possesses no Lewis acidity gave poor performance in the catalytic reaction. With the increase in the amount of oxidant in the reaction mixtures, the conversion of benzyl alcohol increased significantly but the selectivity for benzaldehyde was reduced. For reusability test, the catalytic performance of the re-used samples was maintained within 5-10% after two cycles of reuse without significant loss of activity. Comparison of the catalytic performance of SnM60 in the oxidation of unsaturated primary alcohols and saturated aliphatic primary alcohol towards the corresponding aldehydes showed higher % conversion of the unsaturated primary alcohols than that of the saturated aliphatic primary alcohol